Performing while transforming : Andrew H. Van de Ven's enduring contributions to management scholarship - Bartunek, Jean M.; Garud, Raghu; Langley, Ann; Schilli, Katharina; Sun, Yunchen (Sage, 2025)
This essay pays tribute to Andrew H. Van de Ven's (1945-2022) contributions to management theory and practice. We highlight Andy's views on organizational phenomena as evolving processes and show how he applied these, as well as his own engaged scholarship, to develop novel insights on innovation, and organizational change, among other topics. His approach to scholarship, which involved working to transform existing understandings of management theory and practice even as he performed them in his own academic activities, serves as an enduring legacy for emerging and seasoned scholars in our field.